PENGARUH HARGA POKOK PRODUKSI, BIAYA OPERASIONAL, DAN PENJUALAN BERSIH TERHADAP LABA BERSIH - Fatmasari, Santi; Mustari, Mustari; Ridwan, Rizky; Malik, Rifki Abdul (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
This research aims to determine how operating costs, operating costs and net sales affected the net profits of mining companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2022. The focus of this research is explanatory research. The population of this study was mining companies listed on the Indonesia Stock Exchange (IDX). The research used probability sampling method which then collected 64 mining companies as samples that met the criteria inculuding: listed on the IDX, published financial reports as of December 31, and earned profits during the period of 2021-2022. The study used quantitative information and secondary data. The method for collecting data in this research is the measurement and testing method using financial report data from the IDX. This study adopted path analysis to analyze the data. The results of this research reveal that COGS, operating expenses, and net sales have a significant impact on net income. In addition, net income has a significant impact, while operating costs and COGS do not have an impact.